Thermotolerance Divergence Revealed by the Physiological and Molecular Responses in Two Oyster Subspecies of Crassostrea gigas in China - Ghaffari, Hamze; Wang, Wei; Li, Ao; Zhang, Guofan; Li, Li (Frontiers in Physiology, 2019)
Investigating the physiological mechanisms of closely related species that exhibit distinct geographic distributions and thermal niches is essential for understanding their thermal tolerance capacities and local adaptations in view of climate warming. The variations in upper thermal limits (LT50) under acute heat shock and cardiac activity, standard metabolic rate (SMR), anaerobic metabolite production and molecular responses (expression of molecular chaperones and glycolysis metabolism genes) under increasing temperatures in two oyster subspecies were studied. The populations of two oyster subspecies, Crassostrea gigas gigas and C. gigas angulata, exhibit different latitudinal distributions along the northern and southern coastlines of China, respectively, which experience different environmental conditions. The LT50 was significantly higher, by ~1°C, in the southern than in the northern oysters. In both subspecies, temperature increases had powerful effects on heart rate, SMR and gene expression. The southern oysters had the highest Arrhenius breakpoint temperatures for heart rate (31.4 ± 0.17°C) and SMR (33.09°C), whereas the heart rate (28.86 ± 0.3°C) and SMR (29.22°C) of the northern oysters were lower. The same patterns were observed for the Q10 coefficients. More thermal sensitivity was observed in the northern oysters than in their southern counterparts, as the heat-shock proteins (HSPs) in the northern oysters were expressed first and had a higher induction at a lower temperature than those of southern oysters. Furthermore, different expression patterns of energetic metabolism genes (HK, PK and PEPCK) were observed. In the northern oysters, increasing anaerobic glycolysis genes (PEPCK) and end products (succinate) were found at 36-43°C, indicating a transition from aerobic to anaerobic metabolism and a lower aerobic scope compared with the southern oysters. These two subspecies experience different environmental conditions, and their physiological performances suggested species-specific thermal tolerance windows in which the southern oysters, with mild physiological flexibility, had a higher potential capability to withstand heat stress. Overall, our results indicate that comparing and unifying physiological and molecular mechanisms can provide a framework for understanding the likely effects of global warming on marine ectotherms in intertidal regions.